Higher-dimensional wannier interpolation for the modern theory of the dzyaloshinskii–moriya interaction: Application to co-based trilayers - Hanke, Jan-Philipp; Freimuth, Frank; Bluegel, Stefan; Mokrousov, Yuriy (Journal of the Physical Society of Japan, 2018)
We present an advanced first-principles formalism to evaluate the Dzyaloshinskii–Moriya interaction (DMI) in its modern theory as well as Berry curvatures in complex spaces based on a higher-dimensional Wannier interpolation. Our method is applied to the Co-based trilayer systems IrδPt1−δ=Co=Pt and AuγPt1−γ=Co=Pt, where we gain insights into the correlations between the electronic structure and the DMI, and we uncover prominent sign changes of the chiral interaction with the overlayer composition. Beyond the discussed phenomena, the scope of applications of our Wannier-based scheme is particularly broad as it is ideally suited to study efficiently the Hamiltonian evolution under the slow variation of very general parameters.
CRIS-Team Scopus Importer:2023-03-27